1973
DOI: 10.1029/ja078i022p04731
|View full text |Cite
|
Sign up to set email alerts
|

Ring current particle distributions during the magnetic storms of December 16-18, 1971

Abstract: Although previous measurements have been made of proton distributions in the ring current region, especially those of low‐energy protons from 200 ev to 50 kev by Frank [1967] and of high‐energy protons with energies greater than 100 kev by Davis and Williamson [1966], S3‐A (Explorer 45) is providing the first total proton energy density measurements in the storm‐time ring current region. Detectors aboard S3‐A, which have been briefly described by Longanecker and Hoffman [1973], have yielded data on the proton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(79 citation statements)
references
References 6 publications
3
76
0
Order By: Relevance
“…Protons in the energy range (5-30 keV in this case) of maximum storm time enhancement (Smith and Hoffman, 1974) show the most rapid decay, and eventually develop a minimum in the spectrum characteristic of the quiet-time spectrum (Smith, 1973). The hiah energv nrotons (>100 keV1, which were depleted during the main phase due mostly to adiabatic compression (Williams, 1970), increase in flux during the gradual storm recovery.…”
Section: Oqservationsmentioning
confidence: 88%
See 1 more Smart Citation
“…Protons in the energy range (5-30 keV in this case) of maximum storm time enhancement (Smith and Hoffman, 1974) show the most rapid decay, and eventually develop a minimum in the spectrum characteristic of the quiet-time spectrum (Smith, 1973). The hiah energv nrotons (>100 keV1, which were depleted during the main phase due mostly to adiabatic compression (Williams, 1970), increase in flux during the gradual storm recovery.…”
Section: Oqservationsmentioning
confidence: 88%
“…proton data have previously shown that OE most dynamic energy region of the earth's ring current is from about 10 keV to 100 keV (Smith and Hoffman, 1972;1974;Williams, et al, 1973;Fritz, et al, 1974). …”
Section: Oqservationsmentioning
confidence: 97%
“…Satellite-measured spectra of ion energy density (proton assumed) during the prestorm quiet (Orbit 97 of the Explorer 45 satellite, or S 3 ) and during a large geomagnetic storm (Orbit 102). After Smith and Hoffman (1973). during a quiet period and during an intense geomagnetic storm (Smith and Hoffman, 1973).…”
Section: 2mentioning
confidence: 99%
“…After Smith and Hoffman (1973). during a quiet period and during an intense geomagnetic storm (Smith and Hoffman, 1973).…”
Section: 2mentioning
confidence: 99%
“…Figure 1 contains data from Orbit 99 during the storm which did not develop a symmetric ring current (Cahill, 1972;Smith and Hoffman, 1972). The outbound portion of the orbit in the evening hours displayed some of the usual charactertistics of an inflated magnetic field, a constant negative AB out towards the region of maximum particle energy density, a minimum in the field near the maximum of the protons, and a recovery at larger distances.…”
Section: Field Deformations and Proton Energy Density Distributionsmentioning
confidence: 99%